ACADEMIC SDI: A PROPOSAL FOR THE FEDERAL UNIVERSITY OF PARANÁ (UFPR) - Machado, Adriana Alexandria; Camboim, Silvana Philippi (Boletim de Ciências Geodésicas, 2019)
Although universities conduct research in the SDI field, they have repeatedly erred when storing, preserving, and sharing their geospatial data. The general objective of this research is to develop a proposal for a Spatial Data Infrastructure (SDI) for the graduate programs of the Department of Earth Sciences at Federal University of Paraná (UFPR). In order to initiate the process of implementing UFPR’s academic SDI, a sample of the theses and dissertations of the aforementioned programs was collected. Subsequently, a survey of the metadata of the spatial study areas and publications was conducted, and finally, these metadata were made available as a catalog through GeoNetwork. The metadata, ISO TC-221, OGC and WC3 standards recommended by INDE-BR were adopted, and free and open source software was used. In this paper, the results of the metadata survey and their availability are presented in the form of a catalog, as well as a synthesis of the reflections made during the execution of the research, in order to help define the characteristics of academic SDIs in the country. The cataloging of historical metadata was found to be viable and to facilitate the dissemination of geospatial data to the scientific community.